Advances in computer games : 16th international conference, ACG 2019 Macao, China, August 11-13, 2019 revised selected papers (Lecture Notes in Computer Science / editors Gerhard Goos, Juris Hartmanis ;, 2020)
This book constitutes the refereed post-conference proceedings of the 16th International Conference on Advances in Computer Games, ACG 2019, held in Macao, China, in August 2019. The 12 full papers presented together with 2 invited papers were carefully reviewed and selected from 19 submissions. The selected papers are devoted to topics such as cooperation; single player games; mathematical approaches; nonogram: general and specific approaches; and deep learning.